Efecto de tres abonos orgánicos en el prendimiento y enraizamiento de estacas de Swietenia macrophylla (caoba) en Zungarococha, Iquitos 2020 - Falcon Cometivos, Juan Roberto (2023)
The investigation work was developed in the lands of the Shop of Teaching and Investigation Garden Agrostológico; Ability of Agronomy-UNAP, located in the village of Zúngarococha, with the objective of determining the best gallinaza level, pollinaza and humus in the prendimiento, enraizamiento and I number of hojas/planta of Swietenia macrophylla (Mahogany), the Complete Design was used at random with three (3) treatments and four (4) repetitions with factorial arrangement of 3 x 3. the test of multiple comparisons of Tukey, the population was Also used it was conformed by stakes apical, he/she mediates and basal of Swietenia macrophylla, the sample conformed it 9 plants according to treatments, the evaluation was carried out to the 60 days, being arrived to the following results: With respect to the number of fastened stakes, enraizamiento and I number of hojas/planta the factor a2b1 (it Stakes he/she mediates + gallinaza) the one that better averages present with values of 16 fastened stakes, 43 cm of longitude radicular and 39 leaves for plant was, the best organic payment presently rehearsal was the posture gallinaza, with regard to the hypothesis outlined in the present investigation this it is accepted because if it exists significant effects of the organic payments especially of the gallinaza in the propagation for stakes of the Swietenia macrophylla (Mahogany).